A Questionnaire-based Analysis of Parental Perspectives on Pediatric Cochlear Implant Rehabilitation Services in India - Mansha Parmar; Mukesh Sharma; Santosh Kumar (Journal of Integrated Health Sciences)
Background: Hearing loss has an impact on the development of speech, language, and social skills in children. A cochlear implant is the best option for most of the child’s communication development. Aims and Objectives: The study aimed to analyze the parental perspectives on rehabilitation services offered for pediatric cochlear implant (CI). Materials and Methods: A nonstandardized questionnaire comprising 25 items was created to understand the perspectives of parents of pediatric CI users. Questionnaire was designed in order to examine rehabilitation services such as parental stress, reasons for delay in obtaining services, sources of emotional support and parents’ views of their children post-CI. The questionnaire was posed to 100 parents, and responses were recorded and coded. Results: Qualitative and quantitative analyses based on parents’ responses identified several factors that significantly influenced parental perspectives during each stage. The major factors delaying the decision to go for CI included a fear of surgery, lack of funds for CI and the subsequent rehabilitation process, and limited knowledge. Key concerns were the child’s academic performance and social acceptance. A significant reduction in the parental stress levels was observed following CI surgery. Conclusion: Parents indicated that local support for therapy, financial assistance, and better guidance at each stage would substantially help in lowering stress levels.